2019
DOI: 10.1177/0146167219853844
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Robustness of the Illusory Truth Effect Across Individual Differences in Cognitive Ability, Need for Cognitive Closure, and Cognitive Style

Abstract: People are more inclined to believe that information is true if they have encountered it before. Little is known about whether this illusory truth effect is influenced by individual differences in cognition. In seven studies (combined N = 2,196), using both trivia statements (Studies 1-6) and partisan news headlines (Study 7), we investigate moderation by three factors that have been shown to play a critical role in epistemic processes: cognitive ability (Studies 1, 2, 5), need for cognitive closure (Study 1),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(70 citation statements)
references
References 64 publications
3
53
2
Order By: Relevance
“…This is particularly relevant, as it has been shown that, in Italy, pediatricians are only the third most important source of information on vaccines for pregnant women, and that they are preceded by web sites and word of mouth [ 34 ]. Misinformation lingers in the memory [ 15 , 39 ], and information that has been encountered before is more likely to be believed as true (the so-called illusory truth effect) [ 40 ]. Likewise, correcting misconceptions based on misinformation is not an easy task [ 41 ] and can even backfire [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly relevant, as it has been shown that, in Italy, pediatricians are only the third most important source of information on vaccines for pregnant women, and that they are preceded by web sites and word of mouth [ 34 ]. Misinformation lingers in the memory [ 15 , 39 ], and information that has been encountered before is more likely to be believed as true (the so-called illusory truth effect) [ 40 ]. Likewise, correcting misconceptions based on misinformation is not an easy task [ 41 ] and can even backfire [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, correcting misconceptions based on misinformation is not an easy task [ 41 ] and can even backfire [ 42 ]. Cognitive-based individual differences do not seem to moderate these effects [ 40 ]. Our findings suggest that individual differences in emotional competence might enable people to make a final decision, despite being emotionally aroused.…”
Section: Discussionmentioning
confidence: 99%
“…This test is more elaborate than the basic verbal ability test in Study 1 and 2, hence also serving to demonstrate the robustness of the results. Participants are presented with 4 pictures and 50 words and are instructed to assign each word to one of the pictures (see e.g., De keersmaecker et al, 2020, and Hall et al, 2019, for recent uses of the test). The amount of correct answers is used as an index for cognitive ability ( M = 39.56, SD = 6.44, Cronbach’s α = .89).…”
Section: Methodsmentioning
confidence: 99%
“…Since then, numerous studies have replicated that repetition increases perceived truth, even for statements that contradict people's prior knowledge. Repetition increases truth ratings for implausible false news headlines (De keersmaecker et al, 2019;Pennycook, Cannon, & Rand, 2018), for facts that contradict common knowledge (Brashier, Eliseev, & Marsh, 2020;Brashier, Umanath, Cabeza, & Marsh, 2017;Fazio & Sherry, in press), and there is some evidence that it increases truth ratings equally for all statements regardless of their plausibility (Fazio et al, 2019).…”
mentioning
confidence: 99%